Mix method analysis for analyzing user behavior on logistic company mobile pocket software - Satria Fadil Persada; Farid Afandi; Anak Agung Ngurah Perwira Redi; Reny Nadlifatin; Yogi Tri Prasetyo; Adji Candra Kurniawan (Jurnal Sistem dan Manajemen Industri, 2023)
The present study emphasizes mixed-method analysis, integrating the partial least square structural equation model (PLS-SEM) and customer journey for mobile pocket office improvement in logistic XYZ company. The extension of the unified theory of acceptance and use of technology (UTAUT 2) model by incorporating perceived risk (PR), personal innovativeness (PI), and trust (TR) variables are used. The sample for this study consisted of 243 respondents. Based on the results of the PLS-SEM analysis, two of the eleven tested hypotheses were determined to be rejected. In application usage, the proposed model effectively explained 85.7 per cent of the influence on behavioral intention (BI) and 72.1 per cent on use behavior (UB). The customer journey mapping (CJM) investigation's findings show that fluctuations in the use of mobile pocket office technology in the field are generally brought on by a lot of data entry, sluggish internet connections, and overworked field operations. The XYZ company may acquire suggestions and knowledge for developing further applications due to this inquiry.